2005
DOI: 10.5194/bg-2-205-2005
|View full text |Cite
|
Sign up to set email alerts
|

Control of phytoplankton production by physical forcing in a strongly tidal, well-mixed estuary

Abstract: Abstract.A zero-dimensional model for phytoplanktonic production in turbid, macro-tidal, well-mixed estuaries is proposed. It is based on the description of light-dependent algal growth, phytoplankton respiration and mortality. The model is forced by simple time-functions for solar irradiance, water depth and light penetration. The extinction coefficient is directly related to the dynamics of suspended particulate matter. Model results show that the description of phytoplankton growth must operate at a time re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 64 publications
3
44
0
Order By: Relevance
“…Therefore, turbidity is typically high and consequently light, rather than nutrients, usually controls phytoplankton growth in these regions (SIN et al, 1999). In fact, it has been shown for phytoplankton primary production models that the most significant errors occur when the temporal pattern of light penetration, linked to the tidal cycle of solids settling and resuspension, is neglected (DESMIT et al, 2005). Microcosm experiments recently carried out in the Guadiana upper estuary confirmed that phytoplankton is co-limited by nutrients (mainly nitrogen) during the productive period and by light throughout the year (DOMINGUES, unpublished data).…”
Section: Tidal Variability Of Environmental Drivers Of Phytoplanktonmentioning
confidence: 99%
“…Therefore, turbidity is typically high and consequently light, rather than nutrients, usually controls phytoplankton growth in these regions (SIN et al, 1999). In fact, it has been shown for phytoplankton primary production models that the most significant errors occur when the temporal pattern of light penetration, linked to the tidal cycle of solids settling and resuspension, is neglected (DESMIT et al, 2005). Microcosm experiments recently carried out in the Guadiana upper estuary confirmed that phytoplankton is co-limited by nutrients (mainly nitrogen) during the productive period and by light throughout the year (DOMINGUES, unpublished data).…”
Section: Tidal Variability Of Environmental Drivers Of Phytoplanktonmentioning
confidence: 99%
“…(1) Net Primary Production (NPP) by diatoms (dia) is the fraction of the vertically averaged gross primary production (GPP) which is not used for respiration associated with growth and maintenance, or for cellular excretion (Desmit et al, 2005):…”
Section: Appendix Amentioning
confidence: 99%
“…A consequence of this high turbidity is that photosynthesis is usually severely light limited. Net primary production is possible only when the euphotic-mixing depth ratio remains sufficiently high (Cole et al, 1992;Soetaert et al, 1994;Kromkamp & Peene, 1995;Desmit et al, 2005). In addition, bacterial production and bacterial respiration are often high due to elevated organic carbon loading (Goosen et al, 1999;Gazeau et al, 2005).…”
Section: Introductionmentioning
confidence: 99%